1970
DOI: 10.1042/bj1180695
|View full text |Cite
|
Sign up to set email alerts
|

The use of protamine to study [6,7-3H]-oestradiol-17β binding in rat uterus

Abstract: 1. The binding of [6,7-(3)H]oestradiol-17beta to uteri has been studied by using sucrose-gradient analysis and also the property of oestradiol receptors to form insoluble complexes with protamine. 2. Protamine precipitates the 8S and part of the 4S oestradiol-binding proteins in uterine cytoplasm from mature rats. It does not precipitate the oestradiol-17beta-binding proteins present in cytoplasm from non-target tissues or serum. No tritium-labelled material was precipitated by protamine after equilibration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

1971
1971
1987
1987

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…In all reports except one (38), however, the results show that a very limited number of acceptor sites exist on DNA (37). These estimations of the number of sites are in conflict with certain indirect in vivo (27) (40), or to form nonspecific complexes with various basic proteins (41) or polyamines (42). Such mediated interactions are reduced to a minimum, and even the most purified preparations of estrogen receptors bind to the specific agarose derivatives when experimental conditions reported here, are used.…”
Section: Resultsmentioning
confidence: 58%
“…In all reports except one (38), however, the results show that a very limited number of acceptor sites exist on DNA (37). These estimations of the number of sites are in conflict with certain indirect in vivo (27) (40), or to form nonspecific complexes with various basic proteins (41) or polyamines (42). Such mediated interactions are reduced to a minimum, and even the most purified preparations of estrogen receptors bind to the specific agarose derivatives when experimental conditions reported here, are used.…”
Section: Resultsmentioning
confidence: 58%
“…This may well turn out to be true but at present the gradient centrifugation is still necessary to evaluate 4-5S binding. Steggles and King reported that a 4-5S EBP distinct from the usual 8-1OS or salt-derived 4-5S form was present in uteri of mature rats (18). Furthermore, this 4-5S form disappeared after ovariectomy or hypophysectomy and thus could be very important in breast tumor response to endocrine ablation.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence is available showing that there is specific binding in the 4S region (10) as well as in the 8S (5), but not all investigators have confirmed this result. Under the conditions used in our experiments, only 8S estradiol receptors have been found in the cytosols from uteri of ovariectomized rats (27).…”
mentioning
confidence: 92%